2020
DOI: 10.1109/access.2020.2996981
|View full text |Cite
|
Sign up to set email alerts
|

Improving Financial Time Series Prediction Accuracy Using Ensemble Empirical Mode Decomposition and Recurrent Neural Networks

Abstract: Recurrent neural networks have received vast amount of attention in time series prediction due to their flexibility in capturing dependencies on various scales. However, as in most of the classical forecasting methods, its accuracy is strongly tied to the degree of signal complexity. Specifically, stock market prices are commonly classified to be non-linear, non-stationary and chaotic signals, since they exhibit erratic behavior that conducts a poor performance in the long short-term memory (LSTM). In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…LSTM and Seq2Seq methods are easily adapted to both univariate or multivariate time series prediction (Rebane et al., 2018; Torres & Qiu, 2018). It should be noted that some authors have identified weaknesses and limitations in using machine learning methods in general and LSTM methods in particular for time series forecasting (e.g., Chacón et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…LSTM and Seq2Seq methods are easily adapted to both univariate or multivariate time series prediction (Rebane et al., 2018; Torres & Qiu, 2018). It should be noted that some authors have identified weaknesses and limitations in using machine learning methods in general and LSTM methods in particular for time series forecasting (e.g., Chacón et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The second most significant journal is IEEE Access, this journal maintains a special section highlighting specific topics of IEEE interest. IEEE Access is published by the Institute of Electrical and Electronics Engineers (IEEE) with a concentration area with specialization in the application of science, technology, engineering, and mathematics [26]. There is no doubt that the quality of the IEEE Acess journal has a score of 0.78 in the Q1 category in Computer Science.…”
Section: Significant Published Journalmentioning
confidence: 99%
“…Firstly, in the existing research on forecasting models for natural gas prices, the decomposition of the original series by VMD technology usually only uses onelevel decomposition technology; besides, there is no published research on forecasting natural gas prices by combining secondary decomposition technology with a deep learning forecasting model. In addition, the research on prediction models combining decomposition technology and LSTM models ignores the residual term after decomposition, failing to consider the complex information contained in the residual after modal decomposition and weakening the decomposition efect of data [31][32][33].…”
Section: Introductionmentioning
confidence: 99%